Analisis Faktor Risiko Gangguan Kesehatan Akibat Kondisi Rumah dan Sanitasi Lingkungan di Dusun Karangduren, Kalitirto, Berbah, Sleman Tahun 2011: Studi Manajemen Pengelolaan Rumah Sehat dan Sanitasi Lingkungan - Subagiyono Subagiyono (Poltekkes Kemenkes Yogyakarta, 2012)
In the declaration of Healthy Indonesia 2010, the environment condition is expected to be conducive for the realization of a state which is free from healthrisk factors, have available clean water, have proper sanitation, comprises of healthy housing, have healthy area planning, and establish a communal care for health problems. Based on the data issued by the Ministry of Health in 2005, houses which could be categorized as healthy was only 35 %, and inrural areas the percentage of unhealthy houses is much bigger than those in urban areas. A preliminary study conducted in Puskesmas Berbah found that diarrhea and gastroenteritic, DHF and lung TB were the prominent incidences during 2010 in this area; and also found that three out of five water samples taken from dug well were not fullfiled the regulation. Based on that, this study was aimed to analyze whether house condition and environmental sanitation have the risk factors on health problems in the study area by doing an observational study which employed cross-sectional design. The data from 49 hoses were epidemiologically analysed by using EpiInfo software, and the results conclude that there were positive correlation between temperature (OR 2,78),humidity (OR 1,82), illumination (OR 1,92), and type of house condition (OR 1,82) with the incidence of health problems among the dwellers.